PERENCANAAN STRATEGIK UNTUK TERCAPAINYA AKUNTABILITAS KINERJA INSTANSI PEMERINTAH - Wiwi Idawati (Jurnal Akuntansi Bisnis, 2017)
Accountability and transparency are the main requirements for the creation of good governance (good governance) and in the institutions of democratic governance. To achieve this goal, the preparation of the strategic plan are expected as a starting point to measure the performance of Government. This paper tries to explain the simple functions of strategic planning in the form of feedback in achieving performance accountability of government institutions and how the government runs the media accountable to the public through accounting.Key words : perencanaan strategic, akuntabilitas, transparansi